Sistema de coso i y su incidencia en los costos operativos de la compañía agrolua s.a. en el cantón de Santo Domingo año 2020 - Arellano Pozo, Katherin Mishell (2021)
The present research work called SISTEMA DE COSO I AND ITS INCIDENCE ON THE OPERATING COSTS OF THE COMPANY AGROLUA SA IN THE CANTON OF SANTO DOMINGO YEAR 2020, has the general objective of determining the incidence of the lack of application of the COSO I system on costs Agrolua SA company operations in the Santo Domingo canton in 2020. On the other hand, also verify the internal control executed in each of the operational and management processes. The methodology is quantitative and descriptive in nature, it sought to analyze the data obtained through inductive, deductive and exploratory methods with the help of the questionnaire, survey, direct observation and through management and operational indicators. In this research work, surveys were applied to administrative personnel in order to determine the application of internal control in operational processes and its influence on decision-making, which was obtained as a result that the company does not constantly evaluate and truthful operational processes, the staff does not observe that the processes that were carried out in the internal regulations are complied with and there are no policies that govern the proper management of the company's internal control. A questionnaire was also applied based on COSO I, which showed that there is a total risk of 6.6%, this occurs mainly because the company does not have a manual of procedures. Regarding the profitability indicators, the main finding is that the company has too many operating costs and expenses, which is why it generates little profit.